Prototipe Mesin Peniris Minyak Pada Kerupuk Udang Untuk Menurunkan Kadar Minyak Kerupuk - Nurul Des Ramadhina; Endah Fitriani (Universitas Darul Ulum, 2023)
Shrimp crackers are snacks made from tapioca flour and shrimp. Crackers also have variations of colour, shape, size, smell, taste, crispness, thickness, or nutritional value. Some of the production of ready-to-eat shrimp crackers is made by home industry that still use traditional equipment to reduce the oil content in the cracker. This affects the quality of the crackers which can cause the crackers not durable and smell it is caused by high oil level due to not optimal draining. Therefore this study aims to design a prototype of oil spinner machine for shrimp crackers equipped with an electric motor, a 4x4 keypad as a timer setting, a current sensor and a voltage sensor to calculate the cost of using electric power, the HC-SR04 sensor as a sensor that detects the liquid level in the container, LCD as a monitor, and a buzzer that functions as an alarm when the engine is off and when the oil container is full which will be connected to the arduino uno microcontroller. After testing with different times, the slicing process was succedeed in reducing the oil content in shrimp crackers by 21.55 % and the cost of using electric power on machine was Rp. 0.8444,- per minute and its also equipped with an oil reservoir that can hold an oil level as high as 3 cm so that the machine is more ergonomic that can improve the quality of shrimp cracker production.